Tyrosine Kinase Inhibitors Stimulate HLA Class I Expression by Augmenting the IFNγ/STAT1 Signaling in Hepatocellular Carcinoma Cells - Takahashi, Aya; Umemura, Atsushi; Yano, Kota; Okishio, Shinya; Kataoka, Seita; Okuda, Keiichiro; Seko, Yuya; Yamaguchi, Kanji; Moriguchi, Michihisa; Okanoue, Takeshi; Itoh, Yoshito (Frontiers in Oncology, 2021)
Combination treatment with tyrosine kinase inhibitors (TKIs) and immunotherapies has shown efficacy in the treatment of multiple cancers, but the immunomodulatory effect of TKIs on the tumor cell phenotype remains unknown in hepatocellular carcinoma (HCC). Given that human lymphocyte antigen class I (HLA-I) is essential for tumor antigen presentation and subsequent antitumor immunity, we examined the effects of regorafenib, as well as other TKIs (sorafenib, lenvatinib and cabozantinib) on HLA-I expression in HCC cell lines. Regorafenib increased cell surface HLA-I and β2-microglobulin protein expression in the presence of interferon γ (IFNγ). The expressions of various genes associated with the HLA-I antigen processing pathway and its transcriptional regulators were also upregulated by regorafenib. Furthermore, we found that regorafenib had an activating effect on signal transducers and activators of transcription 1 (STAT1), and that regorafenib-induced HLA-I expression was dependent on the augmented IFNγ/STAT1 signaling pathway. Trametinib, an inhibitor of the extracellular signal-regulated kinase (ERK) kinase MEK, also activated IFNγ/STAT1 signaling and increased HLA-I expression, whereas the phosphatidylinositol 3-kinase (PI3K) inhibitor buparlisib did not. Given that regorafenib directly inhibits Raf/MEK/ERK signaling, the downregulation of the MEK/ERK pathway appears to be one of the mechanisms by which regorafenib promotes STAT1 activation. Sorafenib, lenvatinib, and cabozantinib also showed the same effects as regorafenib, while regorafenib had most potent effects on HLA-I expression, possibly dependent on its stronger inhibitory activity against the MEK/ERK pathway. These results support the clinical combination of TKIs with immunotherapy for the treatment of HCC.